Users' Engagement Toward The Brand Accounts in Instagram Based on The AISAS Model. An Empirical Study Among College Students in North Bandung - Rochman, Encik Adhiva; Iskandar, Budi Permadi (Journal of Business and Management, 2015)
Abstract. Instagram user database has been developing at a stunning rate since it was first launched in 2010. The study concentrates on the part of Instagram social media on impacts by cross communication of Dentsu. The purpose of this research is to identify the user’s engagement toward the brands on Instagram based on their behaviour and how do the users’ behavior toward the brands they follow in light of three initial phases of the model AISAS of Dentsu. The research used the combination of variables that related to user’s engagement whether there is a relationship or association between phases in Attention, Interest, and Search. The main variables taken from the previous research which is each dimension of phase has some of variables. The research has been done starting from June 2015 by using quantitative method. The questionnaires are filled by 300 respondents from Instagram users on the undergraduate students in ITB and UNPAD. The data collection was tested using chi square test and analyzed by using IBM SPSS 20 through statistical analysis. In summary, the respondents’ behavior toward the brands on Instagram has positive relationship and it has positive correlation of the respondents’ behaviour based on the AISAS model. The results indicated that users’ behavior toward brand on Instagram have significantly association with positive correlation. Keywords: Cross communication, AISAS, user engagement, marketing, Instagram.